2020
DOI: 10.1021/acs.biomac.0c01028
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Chemical Features of the Natural Fibrous Material Wood

Abstract: Peak force infrared (PFIR) microscopy is a recently developed approach to acquire multiple chemical and physical material properties simultaneously and with nanometer resolution: topographical features, infrared (IR)-sensitive maps, adhesion, stiffness, and locally resolved IR spectra. This multifunctional mapping is enabled by the ability of an atomic force microscope tip in the peak force tapping mode to detect photothermal expansion of the sample. We report the use of the PFIR to characterize the chemical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…In comparison with the commonly used chemical imaging by Raman microscopy, IR PiFM can reach C 50 times higher spatial resolution. The resolution is also several times higher than what has been reported for thermal expansion AFM-IR (Gusenbauer et al 2020). cellulose and contribute to the recalcitrance of biomass in fractionating and converting it into various products (dos Santos 2013; Michelin et al 2020;Reza et al 2017).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In comparison with the commonly used chemical imaging by Raman microscopy, IR PiFM can reach C 50 times higher spatial resolution. The resolution is also several times higher than what has been reported for thermal expansion AFM-IR (Gusenbauer et al 2020). cellulose and contribute to the recalcitrance of biomass in fractionating and converting it into various products (dos Santos 2013; Michelin et al 2020;Reza et al 2017).…”
Section: Discussionmentioning
confidence: 84%
“…In recent years, a number of highly advanced techniques like tip-enhanced Raman spectroscopy (TERS), infrared atomic force microscopy (AFM-IR), and infrared photo-induced force microscopy (IR PiFM), especially, have provided spectroscopic imaging with nano-scale spatial resolution (Levin and Bhargava 2005;Lewis et al 1995;Nguyen et al 2020;Ogunleke et al 2017;Xiao and Schultz 2018). AFM-IR based on thermal expansion of the material has been applied for studying wood cell wall (Wang et al 2016;Gusenbauer et al 2020) and xylem pit membranes (Pereira et al 2018). Gusenbauer et al (2020) reported a spatial resolution of 16 nm in their measurements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since its invention, PFIR microscopy with 6-10 nm spatial resolution has been applied over various samples, including polymers [62], aerosol particles [64], boron nitride nanotubes and flakes [63,65], yeast cell walls [66], natural fibrous woods [67], shell rocks [68] and perovskites [69,70]. Liquid-phase PFIR has also been developed using the total internal reflection scheme [65,71,72].…”
Section: Peak Force Infrared (Pfir) Microscopymentioning
confidence: 99%
“…Updated versions of AFM-IR instruments with top-down or top-side illumination do not have such limitations in that specimens of arbitrary thickness can be examined on arbitrary substrates. Similarly, the distribution of functional groups in native and chemical modified wood was examined with an excellent spatial resolution of 16 nm [ 60 ].…”
Section: Afm-ir and Ir S-snom Application In Cellulose Materialsmentioning
confidence: 99%